2020
DOI: 10.3390/biom10111474
|View full text |Cite
|
Sign up to set email alerts
|

Targeting P53 as a Future Strategy to Overcome Gemcitabine Resistance in Biliary Tract Cancers

Abstract: Gemcitabine-based chemotherapy is the current standard treatment for biliary tract cancers (BTCs) and resistance to gemcitabine remains the clinical challenge. TP53 mutation has been shown to be associated with poor clinicopathologic characteristics and survival in patients with BTCs, indicating that p53 plays an important role in the treatment of these cancers. Herein, we comprehensively reviewed previous BTC preclinical research and early clinical trials in terms of p53, as well as novel p53-targeted treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 99 publications
2
20
0
Order By: Relevance
“…Pemigatinib (an FGFR2 inhibitor) demonstrated activity in previously treated advanced cholangiocarcinoma based on a phase 2 trial and was approved by the US FDA in 2020 [10], but only 10-15% of patients with iCCA have the FGFR2 fusion gene [11]. Therefore, this treatment gap identifies iCCA as a priority for exploring novel therapeutic drugs or regimens for advanced or refractory iCCA [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pemigatinib (an FGFR2 inhibitor) demonstrated activity in previously treated advanced cholangiocarcinoma based on a phase 2 trial and was approved by the US FDA in 2020 [10], but only 10-15% of patients with iCCA have the FGFR2 fusion gene [11]. Therefore, this treatment gap identifies iCCA as a priority for exploring novel therapeutic drugs or regimens for advanced or refractory iCCA [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported the anti-cancer activity of MDM2i in combination with GSK2830371 in cutaneous melanoma and showed that GSK2830371 potentiates the effect of MDM2i on melanoma cells by increasing the function and stability of p53 in a p53-dependent manner [21]. As more than half of iCCA are WT p53 [13], we investigated the in vitro activity of HDM201 and GSK2830371 in p53 WT iCCA to explore the potential of this combination for future clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…MDM2 has been reported to be associated with tumorigenesis in multiple solid tumors and sarcoma, as it inhibits the function of p53 (a tumor suppressor) via ubiquitination, leading to proteasomal degradation. Targeting MDM2 alone or in combination with other agents could be a therapeutic strategy in cancer treatment [ 16 , 17 ]. However, MDM2 inhibitors are still under investigation in early clinical trials and are clinically unavailable [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Targeting MDM2 alone or in combination with other agents could be a therapeutic strategy in cancer treatment [ 16 , 17 ]. However, MDM2 inhibitors are still under investigation in early clinical trials and are clinically unavailable [ 17 , 18 ]. In addition, the homozygous deletion of CDKN2A and hemizygous of RB1 were observed, and CDK4/6 inhibitors (palbociclib, ribociclib, and abemaciclib) may be an off-label option [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Palliative chemotherapy with cisplatin and gemcitabine (GEM) has been the standard of care for patients with unresectable cancers since 2010 and no breakthrough progress in this challenging disease in the era of targeted therapy and immunotherapy [ 2 ]. In order to serve as a reference for further research to overcome GEM-resistance and provide novel treatment strategies, this Special Issue entitled “Cutting-Edge Research for Exploration of Biomolecules for Gemcitabine-Based Chemoresistant Advanced Bile Duct Cancers: From Basic Study to Clinical Trial” aimed to integrate the cutting-edge research and expand knowledge on a wide range of topics, including bioinformatics [ 3 ], clinical trials [ 4 ], p. 53 [ 5 ], micro-RNA [ 6 ], and other associated studies [ 7 ].…”
mentioning
confidence: 99%